97.1k views
1 vote
Convert the rectangular equation to polar form.Assume a> 0x^2+y^2 -7ay=0

Convert the rectangular equation to polar form.Assume a> 0x^2+y^2 -7ay=0-example-1
User Leyu
by
4.6k points

1 Answer

5 votes

To convert the rectangular equaton to polar form, we use


x=r\cos (\theta),y=r\sin (\theta),r^2=x^2+y^2

we replace x^2 + y^2 by r^2,


r^2-7ay=0

Then, we replace y,


\begin{gathered} r^2-7a(r\sin (\theta))=0 \\ r^2=7a\cdot r\sin (\theta) \\ r\cdot r=7a\cdot r\sin (\theta) \\ r=(7a\cdot r\sin (\theta))/(r) \\ r=7a\cdot\sin (\theta) \end{gathered}

User Tardate
by
5.4k points